Exploring EFL Pre-Service Teachers’ Practices in Learning Material Development - Arunika, Milen; Agustina, Noni (Teacher Training and Education Faculty of Syekh-Yusuf Islamic University Tangerang, 2026)
This study explores how English as a Foreign Language (EFL) pre-service teachers develop English learning materials by applying Tomlinson’s framework for learning materials criteria at a private university. The research addresses the limited literature on material development practices among pre-service teachers, as previous studies have mostly focused on in-service teachers, while this study focuses on learning materials developed by pre-service teachers. Employing a qualitative case study approach, data were collected through semi-structured interviews with three pre-service teachers and document analysis of three sets of learning materials developed during the Language Material Development course. Thematic analysis was applied to identify materials aligned with Tomlinson’s criteria framework, including linked to the curriculum, suitable to learners’ needs, balanced skills, learners’ prior knowledge, cooperative learning opportunities, targeted to communicative purposes, cultural integration, and succinct instructions. Findings indicate that all analysed materials met the framework’s principles, effectively addressing diverse learning styles, balancing language skills, communicative purposes, and cooperative learning. The study contributes insights for teacher education programs, policymakers, and material developers, emphasizing the criteria of Tomlinson’s learning materials framework for developing engaging EFL materials.